2005
DOI: 10.1111/j.0022-202x.2004.23545.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Mouse Skin Morphology and Specific Effects of Sex Steroids and Dehydroepiandrosterone

Abstract: Sex steroids play an important role in skin morphology and physiology. To evaluate the specific effects of sex steroids, the thickness of each skin layer was measured in intact and gonadectomized (GDX) male and female mice, as well as in GDX animals treated for 3 wk with 17beta-estradiol (E2), dihydrotestosterone (DHT), or their precursor dehydroepiandrosterone (DHEA). Morphological analysis shows that the dorsal skin of intact male is thicker than in the female, whereas the epidermis and hypodermis are thicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 21 publications
12
109
2
5
Order By: Relevance
“…Skin is not traditionally considered a sex hormone-responsive tissue; however, studies have shown that such hormones can have a significant influence on the skin. Studies by Azzi et al (39) showed gender differences in mouse skin morphology, an effect of gonadectomy on skin structure, and an influence of exogenous estrogen and estrogen precursors on skin histology. Postmenopausal women with diminished systemic estrogen production show significant changes in the skin, including delayed wound healing, skin thinning, and increased wrinkling, all of which can be reversed with hormone replacement therapy (40).…”
Section: Discussionmentioning
confidence: 99%
“…Skin is not traditionally considered a sex hormone-responsive tissue; however, studies have shown that such hormones can have a significant influence on the skin. Studies by Azzi et al (39) showed gender differences in mouse skin morphology, an effect of gonadectomy on skin structure, and an influence of exogenous estrogen and estrogen precursors on skin histology. Postmenopausal women with diminished systemic estrogen production show significant changes in the skin, including delayed wound healing, skin thinning, and increased wrinkling, all of which can be reversed with hormone replacement therapy (40).…”
Section: Discussionmentioning
confidence: 99%
“…5 mm) (Sensyu Kagaku, Tokyo) were used. The column oven was set to 30 C. The elution program was a linear gradient with 87.5:12:0.5 (vol/vol/vol) chloroform:methanol:triethylamine buffer (pH 3, 1 M formic acid) at t ¼ 0 min to 28:60:12 (vol/vol/vol) at t ¼ 26 min. The mobile phase was kept at 28:60:12 (vol/vol/vol) chloroform:methanol:triethylamine for a further 4 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that gender differences affect skin morphology due to sex hormones. 30) Estrogen, a famous female Cer, ceramides; Ch, cholesterol hormone, increases the skin collagen content and thus maintains skin thickness and elasticity, and that maintains the skin water content.…”
Section: Content Of Ceramides In Stratum Corneummentioning
confidence: 99%
“…A recent study has demonstrated that in response to Staphylococcus aureus skin infections in C57BL/6J mice, dermal preadipocytes proliferate and protect against the infection (31). In addition, a previous study has shown that sex plays an important role in skin morphology and physiology (32). Based on these studies, we hypothesized a similar proliferation against GAS skin infections; also, we wanted to determine whether there are any marked sex-based differences in this proliferation.…”
Section: Resultsmentioning
confidence: 96%